Induction of Trained Immunity by Recombinant Vaccines - Covián, Camila; Ríos, Mariana; Berríos-Rojas, Roslye V.; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2021)
Vaccines represent an important strategy to protect humans against a wide variety of pathogens and have even led to eradicating some diseases. Although every vaccine is developed to induce specific protection for a particular pathogen, some vaccine formulations can also promote trained immunity, which is a non-specific memory-like feature developed by the innate immune system. It is thought that trained immunity can protect against a wide variety of pathogens other than those contained in the vaccine formulation. The non-specific memory of the trained immunity-based vaccines (TIbV) seems beneficial for the immunized individual, as it may represent a powerful strategy that contributes to the control of pathogen outbreaks, reducing morbidity and mortality. A wide variety of respiratory viruses, including respiratory syncytial virus (hRSV) and metapneumovirus (hMPV), cause serious illness in children under 5 years old and the elderly. To address this public health problem, we have developed recombinant BCG vaccines that have shown to be safe and immunogenic against hRSV or hMPV. Besides the induction of specific adaptive immunity against the viral antigens, these vaccines could generate trained immunity against other respiratory pathogens. Here, we discuss some of the features of trained immunity induced by BCG and put forward the notion that recombinant BCGs expressing hRSV or hMPV antigens have the capacity to simultaneously induce specific adaptive immunity and non-specific trained immunity. These recombinant BCG vaccines could be considered as TIbV capable of inducing simultaneously the development of specific protection against hRSV or hMPV, as well as non-specific trained-immunity-based protection against other pathogenic viruses.